Technological prospecting of the economic and industrial importance of coco and chia in Brazil (Research, Society and Development, 2021)
Despite showing a drop in production, Brazil is one of the largest coconut producers in the world, however chia seeds are still little produced. This research sought to investigate the market for these foods through mapping on websites and the INPI. There were a total of 19 coconut industries, with the Northeast as its epicenter, and 12 with chia, led by the Southeast. 18 products with coconut and 9 with chia were found. The value of coconut was higher in regions where its production is insignificant. The recent cultivation of chia has made market investigation impossible to date. There are 359 patent applications with the general descriptor "coconut", while "chia" presented only 10. The search for patents relating the two foods did not yield results. The study shows the feasibility of developing products that include the analyzed raw materials , as well as the registration of patents.